The impact of the independence of the auditor to practice accounting conservatism Applied research in the financial sector companies listed on the Iraq Stock Exchange - خضير, بشرى فاضل; حلو, جعفر عبد الحسين (Journal of Economics and Administrative Sciences, 2016)
The study aims to verify the independence of auditors working in companies and offices of the Iraqi audit, and measure the level of accounting conservatism in the financial statements of banks and insurance companies listed on the Iraq Stock Exchange, as well as a statement after the independence of the auditor on accounting conservatism in the financial statements of banks and insurance companies listed on the market Iraq Stock Exchange, as it has been measuring the independence of the auditor using the survey form was auditors working in the Iraqi audit firms were measured the level of accounting conservatism for companies sample using a form( Basu) was a statement after variables through the use of statistical models in a manner least squares model and linear regression as well as model test (Binomial) and after testing hypotheses The research found a set of conclusions, represented the existence of an acceptable level for some independence audit at the offices of companies and the Iraqi audit factors, and an acceptable level of conservatism accounting in accounting policies in the financial sector companies listed on the Iraq Stock Exchange, as well as and there is a significant correlation between some of the independence of the auditor and the accounting conservatism agents. Find and gave a number of recommendations, it represented the need to open a large audit firms, and the emphasis on legislative and regulatory bodies for the auditing profession in Iraq, including the Council on auditing profession companies and offices checking the existence of an acceptable level of accounting conservatism in the financial reports are audited